The shifting landscape of post-conviction review in New Zealand: reflections on the prospects for the Criminal Cases Review Commission - Hoyle, C (Routledge, 2020)
Concerns about the lack of integrity in the criminal process, and resulting miscarriages of justice, dented public confidence in the New Zealand justice system and its limited post-conviction review procedures. In turn, this generated an appetite for a Criminal Cases Review Commission, modelled on the English and Scottish Commissions. This article draws on evidence from the English Commission to consider the prospects for the New Zealand Commission given its proposed investigative powers, its criteria for referring cases to the appeal court and its remit beyond casework. It argues that while it is assumed that the New Zealand Commission will have more liberal powers to refer cases back to the appeal court than its sister Commission in England, evidence suggests that its decisions will be similarly restricted by the Court's statutory obligations and its evolving jurisprudence.